Childhood deaths from external causes in Estonia, 2001-2005 - Soonets Ruth; Lang Katrin; Väli Marika; Talumäe Marika; Grjibovski Andrej M (BMC, 2007)
Abstract Background In 2000, the overall rate of injury deaths in children aged 0-14 was 28.7 per 100000 in Estonia, which is more than 5 times higher than the corresponding rate in neighbouring Finland. This paper describes childhood injury mortality in Estonia by cause and age groups, and validates registration of these deaths in the Statistical Office of Estonia against the autopsy data. Methods The data on causes of all child deaths in Estonia in 2001-2005 were abstracted from the autopsy protocols at the Estonian Bureau of Forensic Medicine. Average annual mortality rates per 100,000 were calculated. Coverage (proportion of the reported injury deaths from the total number of injury deaths) and accuracy (proportion of correctly classified injury deaths) of the registration of causes of death in Statistical Office of Estonia were assessed by comparing the Statistical Office of Estonia data with the data from Estonian Bureau of Forensic Medicine. Results Average annual mortality from external causes in 0-14 years-old children in Estonia was 19.1 per 100,000. Asphyxia and transport accidents were the major killers followed by poisoning and suicides. Relative contribution of these causes varied greatly between age groups. Intent of death was unknown for more than 10% of injury deaths. Coverage and accuracy of registration of injury deaths by Statistical Office of Estonia were 91.5% and 95.3%, respectively. Conclusion Childhood mortality from injuries in Estonia is among the highest in the EU. The number of injury deaths in Statistical Office of Estonia is slightly underestimated mostly due to misclassification for deaths from diseases. Accuracy of the Statistical Office of Estonia data was high with some underestimation of intentional deaths. Moreover, high proportion of death with unknown intent suggests underestimation of intentional deaths. Reduction of injury deaths should be given a high priority in Estonia. More information on circumstances around death is needed to enable establishing the intent of death.